MENINGKATKAN DISIPLIN BELAJAR PADA ANAK DENGAN METODE OUTBOND - Suryadi Suryadi; Nur Imam Mahdi (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2020)
This research is a Classroom Action Research (PTK). The research subjects were students of group B TK PWS Surokarsan. The data collection techniques used were observation, documentation and interviews. The objectives of this classroom action research are (1) Knowing how effective outbound activities are to improve children's discipline (2) Knowing and implementing outbound methods for improving children's learning time discipline (3) Designing outbound activities that are interesting and beneficial for children, namely increasing children's learning discipline. (4) Implementing the benefits of playing outbound for the improvement of children's learning time discipline. The results of the study concluded that the Outbound method can increase children's interest in learning, especially learning calistung in group B TK Sulthoni students with an increase in the cycle of attendance of children. Cycle I 40% Cycle II 60% Cycle III 90% Compliance with the rules III 85% Discipline of children to learning time Cycle I 45% Cycle II 65% Cycle III 85% Responsibility of children to game tools Cycle I 60% Cycle II 70% Cycle III 90% Children's reactions to outbound activities Cycle I 70% Cycle II 80% Cycle III 90% Children tidy up places and play tools Cycle I 50% Cycle II 70% Cycle III 85% Obey teacher orders and run it Cycle 50% Cycle II 75% Cycle III 80%. Keywords: Discipline, Children and Outbound